Effects of high levels of dietary niacin from nicotinic acid on growth and meat quality of finishing pigs raised during summer - Flohr, Joshua R.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Dritz, Steven S.; Goodband, Robert D.; Houser, Terry A.; Felder, C. A.; Prusa, K. J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 1,232 pigs (PIC 337 × 1050; initially 59.4 lb) were used in a 98-d study to evaluate the influence of increasing dietary niacin supplementation on growth, body temperatures, and meat quality of pigs raised in a commercial facility during the summer. There were 28 pigs per pen and 11 pens per treatment. Basal diets contained corn, soybean meal, and dried distillers grains with solubles (DDGS). The four dietary treatments were formed by adding increasing levels of nicotinic acid as the source of niacin (Lonza, Allendale, NJ) at 14, 172, 331, and 490 mg/lb of complete feed. On d 57, 58, and 59, rectal temperatures and skin temperatures on the top of the shoulder and rump were collected from 2 pigs per pen (1 barrow and 1 gilt). On d 98, 2 pigs per pen (1 barrow and 1 gilt) were visually selected as the heaviest pigs in the pen and were harvested for carcass and meat quality data. Carcass traits, pH decline, and subjective loin color and marbling scores were measured at a commercial abattoir. Afterward, a 15.7-in. segment of the loin was used for meat quality analysis, including measurements of ultimate pH and purge loss. Boneless chops (1 in. thick) were cut from the loin segment and were used to determine 24-h drip loss, subjective color and marbling, objective lean color values (L*, lightness; a*, redness; and b*, yellowness), and muscle niacin concentrations. Average daily temperatures within the barn ranged from 63.8 to 85.5°F throughout the length of the study, with daily low temperatures from 59.9 to 81.0°F and daily high temperatures from 66.1 to 93.3°F. Overall, temperature was cooler than expected for the facility compared with normal seasonal increases associated with the summer months. Time × day interactions (P < 0.01) were observed for rectal, shoulder, and rump temperatures; however, body temperature was not consistently influenced by dietary niacin concentrations during the collection period. Overall (d 0 to 98), increasing dietary niacin did not influence ADG or F/G, but it tended (linear; P = 0.07) to increase ADFI. Increasing niacin supplementation did not influence carcass traits; however, for meat quality, it did increase (linear; P < 0.01) pH decline at 45 min and 21 h postmortem. Increases (linear; P < 0.05) in a* and b* were observed for chops from pigs fed increasing niacin, but subjective chop color scores were not affected by increasing niacin supplementation. In summary, dietary niacin above the animal’s requirement estimate did not consistently influence rectal or skin temperatures and had negligible influences on growth performance, carcass traits, and meat quality parameters.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Heat stress; Niacin; Nicotinic acid; Finishing pig